Kontribusi Ajaran Islam Tentang Hak Politik Perempuan (Mazahib, 2016)
The purpose of this study is to determine and to analyze how the contribution of Islamic teachings on women's political rights. Contributions of Islam on women's political rights has been long existed, Islam never restricts women’s creativity in any field as long as it does not violate the nature as a woman. If she has married, responsibilities as a wife and mother of her children should not be forgotten. In Islam, either man or woman has the right to organize, fight and defend, and the right to participate in the diplomatic and political agreements. The constraints against women is the lack of support from the women themselves for the sake of fulfilling a quota of 30% which is until this time it has not happened yet. Besides, the lack of knowledge for their representation as women in the political domain which has the real influence to the prosperous society The efforts being made should have been done well, the government should always pay attention to the representation of women in many ways. In the political domain, political parties should be one of the institutions which empower women who has a capability in political struggle.Keywords: Contributions Teaching of Islam, Women's Political Rights.